2013
DOI: 10.1186/1746-6148-9-201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diets with a high content of greaves-meal protein or carbohydrates on faecal characteristics, volatile fatty acids and faecal calprotectin concentrations in healthy dogs

Abstract: BackgroundResearch suggests that dietary composition influences gastrointestinal function and bacteria-derived metabolic products in the dog colon. We previously reported that dietary composition impacts upon the faecal microbiota of healthy dogs. This study aims at evaluating the dietary influences on bacteria-derived metabolic products associated with the changes in faecal microbiota that we had previously reported. We fed high-carbohydrate starch based (HCS), [crude protein: 194 g/kg, starch: 438 g/kg], hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 51 publications
7
26
1
Order By: Relevance
“…In that study, the high protein diet group was fed about a 2.3 times higher protein content than the commercial diet group. 47 In contrast, in our current study, we observed higher fecal concentrations of acetate and propionate in the healthy dogs that were fed a higher protein content in their diet. Moreover, the difference in the amount of protein content in our study was much less (1.3 times higher in the healthy dogs) than that study.…”
Section: Correlations Of Fecal Scfas and The Fecal Microbiotacontrasting
confidence: 90%
“…In that study, the high protein diet group was fed about a 2.3 times higher protein content than the commercial diet group. 47 In contrast, in our current study, we observed higher fecal concentrations of acetate and propionate in the healthy dogs that were fed a higher protein content in their diet. Moreover, the difference in the amount of protein content in our study was much less (1.3 times higher in the healthy dogs) than that study.…”
Section: Correlations Of Fecal Scfas and The Fecal Microbiotacontrasting
confidence: 90%
“…Diarrhoea was also observed in dogs fed high level animal-derived protein (greaves meal; >50 g protein/100 g diet DM) according to previous studies [26, 61]. Diet-induced effect on faecal consistency has been associated with an increase in Clostridium perfringens in faecal samples [27] as well as ileal chyme [26] in laboratory dogs.…”
Section: Discussionmentioning
confidence: 62%
“…However, butyrate levels and Roseburia abundance did not significantly differ between CD1 and HMB samples. The content of dietary fibre has been associated with increased concentrations of dogs’ faecal SCFAs, including butyrate in one study [11], although a similar association has not been observed in other studies [61, 62]. An in-vitro study using faecal samples from cheetahs demonstrated that cartilage entering the large intestine may have a similar effect on the SCFA profile as plant fibre [63].…”
Section: Discussionmentioning
confidence: 99%
“…pigs), commonly thought as low-grade meat meal, lead to higher pH, decrease in propionic and acetic acids and increase in branched-chain fatty acids and valeric acid and changes in faecal total volatile fatty acids, higher faecal canine calprotectin concentration which was associated with increased valeric acid concentration. In addition, all studied dogs fed high-protein greaves-meals developed diarrhoea [36].…”
Section: Effect Of Diet On Microbiotamentioning
confidence: 97%